trkA, CGRP and IB4 expression in retrogradely labelled cutaneous and visceral primary sensory neurones in the rat. - Bennett, D; Dmietrieva, N; Priestley, J; Clary, D; McMahon, S (1996)
The pattern of trkA expression in relation to other neurochemical markers (CGRP and IB4) was investigated in primary sensory neurones innervating either the skin or bladder. Retrograde tracing using the fluorescent marker Fast Blue was performed followed by histochemistry. A greater proportion of visceral afferents compared with cutaneous afferents were trkA-immunoreactive (75% and 43%, respectively). CGRP expression correlated with trkA expression in that it was higher in visceral afferents than cutaneous afferents (69% and 51%, respectively). IB4 expression was negatively correlated with trkA expression, being lower in visceral afferents compared with cutaneous afferents (29% and 43%, respectively). The results emphasise the heterogeneity of trkA expression (and hence nerve growth factor, sensitivity) in afferents innervating different targets, and furthermore suggest that it is predominantly the CGRP-expressing population of primary afferents that express trkA.